1990
DOI: 10.1042/bst0181041
|View full text |Cite
|
Sign up to set email alerts
|

The antioxidant hypothesis of cardiovascular disease: epidemiology and mechanisms

Abstract: Plasma levels of major essential antioxidants were determined in representative random samples of middle-aged men from 16 European study populations which differed up to 6-fold in age-specific mortality from ischaemic heart disease (IHD). In 12 study populations having total plasma cholesterol in the medium range (5.7-6.2 mmol/l) and usual blood pressure, both these classical risk factors lacked a significant correlation to IHD mortality, whereas the absolute level of vitamin E (alpha-tocopherol) showed a stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
126
0
2

Year Published

1995
1995
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(128 citation statements)
references
References 4 publications
0
126
0
2
Order By: Relevance
“…Reactive oxygen species (ROSs) play important roles in degenerative or pathological processes in conditions such as aging (Burns et al, 2001), cancer, coronary heart disease, Alzheimer's disease (Ames et al, 1983;Gey, 1990;Diaz et al, 1997), neurodegenerative disorders, atherosclerosis, cataract formation, and inflammation (Aruoma, 1998). Excessive production of ROSs may lead to oxidative damage to proteins, DNA, genomic instability and other macromolecules, accumulation of which with time favors the acquisition of mutations and ultimately results in the cellular transformation to cancer cells (Vera-Ramirez et al, 2011).…”
Section: Indirect Anticancer Effects Via Immunostimulatingmentioning
confidence: 99%
“…Reactive oxygen species (ROSs) play important roles in degenerative or pathological processes in conditions such as aging (Burns et al, 2001), cancer, coronary heart disease, Alzheimer's disease (Ames et al, 1983;Gey, 1990;Diaz et al, 1997), neurodegenerative disorders, atherosclerosis, cataract formation, and inflammation (Aruoma, 1998). Excessive production of ROSs may lead to oxidative damage to proteins, DNA, genomic instability and other macromolecules, accumulation of which with time favors the acquisition of mutations and ultimately results in the cellular transformation to cancer cells (Vera-Ramirez et al, 2011).…”
Section: Indirect Anticancer Effects Via Immunostimulatingmentioning
confidence: 99%
“…Fresh organic fruits, vegetables and herbal teas that are rich in natural antioxidant compounds have been associated with the prevention of various types of cancer and cardiovascular diseases (Willcox et al, 2004). Epidemiological studies have demonstrated an inverse association between intake of fruits and vegetables and mortality from age related diseases, such as coronary heart disease and cancer, which may be attributed to their antioxidant activity (Cragg et al, 1997;Eberhardt et al, 2000;Gey, 1990;Kris-Etherton et al, 2002;Willett, 1994). Different studies have suggested that synthetic antioxidants, such as Butylated hydroxyanisole ( BHA) butylated hydroxytoluene (BHT), need to be replaced with natural antioxidants, as they were found to be toxic and carcinogenic in tested animal models (Ito et al, 1986;Safer and Al-Nughamish, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence indicates that experimental atherosclerosis and foam cell formation can be effectively retarded by antioxidants (10)(11)(12). In addition, supplementation of human subjects with antioxidants has been shown to increase the resistance of their low density lipoproteins to oxidation and to protect against arteriosclerosis (13)(14)(15)(16). As antioxidants, tocopherols may stimulate in some cases cell proliferation by removing inhibitory lipid peroxides (17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%